2012
DOI: 10.1063/1.3702203
|View full text |Cite
|
Sign up to set email alerts
|

Sheet-like assemblies of spherical particles with point-symmetrical patches

Abstract: We report a computational study on the spontaneous self-assembly of spherical particles into twodimensional crystals. The experimental observation of such structures stabilized by spherical objects appeared paradoxical so far. We implement patchy interactions with the patches point-symmetrically (icosahedral and cubic) arranged on the surface of the particle. In these conditions, preference for self-assembly into sheet-like structures is observed. We explain our findings in terms of the inherent symmetry of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…However, continuing the dialysis led to the formation of stacked sheets into bundled structures (see Figure b showing 3 sheets stacked) . This is in analogy with the 2D crystal formation in keplerates (see later) and apoferritin particles, driven by the anisotropic distribution of the interacting patches …”
Section: Self‐assembled 2d Colloidal Nanosheetssupporting
confidence: 52%
See 2 more Smart Citations
“…However, continuing the dialysis led to the formation of stacked sheets into bundled structures (see Figure b showing 3 sheets stacked) . This is in analogy with the 2D crystal formation in keplerates (see later) and apoferritin particles, driven by the anisotropic distribution of the interacting patches …”
Section: Self‐assembled 2d Colloidal Nanosheetssupporting
confidence: 52%
“…There the self‐assembly of macroanionic clusters was attributed to the H‐bondings, directed by water molecules. Recent theoretical studies using Monte Carlo simulations have shown that the patchy distribution of interacting sites on the clusters is responsible for spherical formation . On the other hand, reverse emulsion mediated assembly of spherical particles into colloidosomes has been shown to display plasmonic broadband absorption properties …”
Section: Self‐assembled Capsidsmentioning
confidence: 99%
See 1 more Smart Citation
“…11−14 The particles can also be used as model system to study complex interaction of globular proteins, inorganic macromolecules such as polyoxometalates, and virus capside formation by mimicking anisotropic patchy interactions. 15 Patchy colloids can be synthesized by modifying a part of the particle surface through chemical or physical modifications. Different methods such as sputtering of metal films, 16 stamp coating of polymer, 17 particle lithography, 18,19 and glancing angle deposition 20,21 have been employed to prepare patchy particles.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Other authors studied the assembly of Keplerates in sheet-like structures using Monte Carlo methods. 49 Since anionic ligands coordinating to an already anionic Keplerate appears paradoxical, and given the key role that Keplerate-ligand interactions play in tuning the chemical properties of the inner surface of these capsules, in this manuscript we are reporting a detailed study of the interaction between the Mo 132 capsule and different types of ligands. The analysis relies on the bonding energy decomposition analysis (EDA).…”
mentioning
confidence: 99%